2023
DOI: 10.1002/ps.7802
|View full text |Cite
|
Sign up to set email alerts
|

Host‐virus interaction between tobacco mild green mosaic virus strain U2 and tropical soda apple resulting in systemic hypersensitive necrosis and the host range, survival, spread, and molecular characterization of the virus

Raghavan Charudattan,
Ernest Hiebert,
Matthew S. Pettersen
et al.

Abstract: BackgroundTobacco mild green mosaic virus strain U2 (TMGMV‐U2) is a registered active ingredient in a bioherbicide to control tropical soda apple (TSA), Solanum viarum, an invasive weed. As required for registration, we developed empirical data on the host‐virus interaction and the virus's host range, survival, spread, and genomic sequence.ResultsTMGMV‐U2 killed TSA plants by causing systemic hypersensitive necrosis (SHN). It elicited local lesions in inoculated leaves which was followed by the plant's wilting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(33 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Our data indicated a 'moderately broad' host range for TMGMV-U2 (Tables 1 and 2). These data and the published host range of TMGMV confirmed that the majority of TMGMV-susceptible plants were in the Solanaceae, 22,26 and that TMGMV-U2 is undoubtedly a Solanaceae-adapted virus. 56 The SHN was expressed only in a small number of species, all in the Solanaceae.…”
Section: Epa Registration: Considerations Of Possible Riskssupporting
confidence: 64%
See 4 more Smart Citations
“…Our data indicated a 'moderately broad' host range for TMGMV-U2 (Tables 1 and 2). These data and the published host range of TMGMV confirmed that the majority of TMGMV-susceptible plants were in the Solanaceae, 22,26 and that TMGMV-U2 is undoubtedly a Solanaceae-adapted virus. 56 The SHN was expressed only in a small number of species, all in the Solanaceae.…”
Section: Epa Registration: Considerations Of Possible Riskssupporting
confidence: 64%
“…22 In a preliminary host range study with solanaceous plants of 32 different species, TMGMV-U2 elicited host responses ranging from asymptomatic infection (ELISA-positive) to mild systemic mosaic and local lesions. More extensive host range data are presented in Charudattan et al 22 Among the susceptible species, only TSA was killed completely and in a characteristic and predictable manner as described above. Multiple greenhouse trials and two small-scale field trials in two counties of Florida confirmed the efficacy of TMGMV-U2 as a bioherbicide candidate.…”
Section: The Bioherbicide Proof Of Conceptmentioning
confidence: 99%
See 3 more Smart Citations